Growth parameters at birth mediate the relationship between prenatal manganese exposure and cognitive test scores among a cohort of 2- to 3-year-old Bangladeshi children. (3rd May 2018) - Lee, Jane J; Valeri, Linda; Kapur, Kush; Ibne Hasan, Md Omar Sharif; Quamruzzaman, Quazi; Wright, Robert O; Bellinger, David C; Christiani, David C; Mazumdar, Maitreyi
Abstract: Background: Our previous study demonstrated that prenatal manganese exposure is associated with cognitive test scores among a cohort of 2- to 3-year-old Bangladeshi children. This study tested the hypothesis that the adverse effects of manganese are mediated through poor prenatal growth. Methods: Pregnant mothers were enrolled in a birth cohort in Bangladesh between 2008 and 2011, and children were followed at birth and age 20–40 months. Manganese concentration was measured in umbilical cord blood. Anthropometric measurements (weight, length, head circumference) were assessed at delivery. Children's cognitive development was assessed at age 20–40 months using the Bayley Scales of Infant and Toddler Development—Third Edition. Using recently developed statistical approaches that estimate mediation and interaction effects simultaneously, we evaluated whether the association between cord blood manganese and cognitive score was mediated through anthropometric measures at birth. Results: This analysis included 764 mother–child pairs. Higher manganese concentration was associated with lower cognitive score [ β =–0.61, standard error (SE)=0.23, p = 0.009]. Among the birth measures, we found a significant indirect effect only through birth length ( β =–0.10, SE = 0.03, p = 0.001). We also found evidence of mediated interaction (both mediation and interaction, β =–0.03, SE = 0.01, p = 0.01) with birth length in the association between cord blood manganese and cognitive score. The overall proportion mediated by birth length was 33% ( p = 0.02) and the proportion attributed to interaction was 11% ( p = 0.04). We did not find evidence of a mediating effect through birth weight or head circumference. Conclusions: Our findings confirm that prenatal growth, particularly birth length, contributes to the overall effect of environmental manganese exposure on a child's cognitive development.